SOCIAL EXCHANGE THEORY - Kh. F. Akramov; Kokanboeva G. S. (European Science Publishing, 2023)
This article is about the social conversion theory of George Homans and Peter Blau. In this book by Homans (Homans G. C. Human Group, New York, 1950), social exchange theory is a model for interpreting society as a series of interactions between people based on the assessment of rewards and punishments. According to this view, our interaction is determined by the rewards or penalties received by others, which we evaluate (consciously or unconsciously) using a model of cost-benefit analysis. Homans theory is based on the rules of mutual exchange of rewards (positive support) and punishments (negative support). Humans divide research objects into groups. In the process of studying these groups, the sociologist determines the dependence of the feelings of their members on their actions. The reasoning cited in the article is that theories are still important and desirable today.
Keywords: action, behavior, reward, success, action, value, incentive, deprivation, costs, result of action, income, approval, aggression, rationality.